Dietary and lifestyle determinants of malondialdehyde DNA adducts in a representative sample of the Florence City population. (9th March 2016) - Saieva, Calogero; Peluso, Marco; Palli, Domenico; Cellai, Filippo; Ceroti, Marco; Selvi, Valeria; Bendinelli, Benedetta; Assedi, Melania; Munnia, Armelle; Masala, Giovanna
Abstract : Malondialdehyde (MDA), a biomarker of lipid peroxidation and oxidative stress, is a mutagenic and carcinogenic compound that can react with DNA to form several types of DNA adducts including the deoxyguanosine adduct (M1 dG). The aim of this cross-sectional study was to evaluate the association between individual dietary and lifestyle habits and M1 dG levels, measured in peripheral leukocytes in a large representative sample of the general population of Florence City (Italy). Selected anthropometric measurements, detailed information on dietary and lifestyle habits and blood samples were available for 313 adults of the Florence City Sample enrolled in the frame of European Prospective Investigation into Cancer and nutrition (EPIC) study. A multivariate regression analysis adjusted for selected individual characteristics possibly related to M1 dG levels (sex, age, BMI, smoke, physical activity level, education level, total caloric intake and a Mediterranean dietary score) was performed to estimate the association between these parameters and M1 dG levels. M1 dG levels were significantly higher in women ( P = 0.014) and lower in moderately active or active subjects ( P = 0.037).We also found a significant inverse association with the Modified Mediterranean dietary score ( P for trend = 0.049), particularly evident for the highest categories of adherence. Our results indicate that M1 dG levels can be modulated by selected individual characteristics such as gender, physical activity and a Mediterranean dietary pattern.